Evaluation Culture and Perceived Satisfaction in Students of the Faculty of Education of the Universidad Nacional Mayor de san marcos - Mendoza Hidalgo Mary Liz; Abarca Arias Yessika Madelaine; Espinoza Moreno Tula Margarita; Soto Hilario Juvita Dina; Inga Arias Manuel Augusto (Migration Letters, 2023)
In the present investigation, the relationship between the evaluative culture and the satisfaction perceived in the students of the Faculty of Education of the Universidad Nacional Mayor de San Marcos was studied. The sample consisted of 259 students, to whom two questionnaires were applied to measure study variables: evaluative culture and perceived satisfaction. The results obtained were analyzed at the descriptive level and at the inferential level according to the objectives and the formulated hypotheses. At the descriptive level, frequencies and percentages were used to determine the predominant levels of the study variables; also performed a correlational analysis between the study variables using non-parametric statistics, given that the data have been measured with ordinal scales and as such the Spearman s statistic has been used. Likewise, statistical tests were applied to determine the correlation between the variables. The results of the descriptive, correlational analyzes supported by the theoretical framework of the study corroborated the relationship between Institutional Evaluative Culture and Perceived Satisfaction, in the context of university education.